An updated overview of clinical guidelines for the management of non-specific low back pain in primary care - Koes, Bart W. (Springer-Verlag, 2010)
The aim of this study was to present and compare the content of (inter)national clinical guidelines for the management of low back pain. To rationalise the management of low back pain, evidence-based clinical guidelines have been issued in many countries. Given that the available scientific evidence is the same, irrespective of the country, one would expect these guidelines to include more or less similar recommendations regarding diagnosis and treatment. We updated a previous review that included clinical guidelines published up to and including the year 2000. Guidelines were included that met the following criteria: the target group consisted mainly of primary health care professionals, and the guideline was published in English, German, Finnish, Spanish, Norwegian, or Dutch. Only one guideline per country was included: the one most recently published. This updated review includes national clinical guidelines from 13 countries and 2 international clinical guidelines from Europe published from 2000 until 2008. The content of the guidelines appeared to be quite similar regarding the diagnostic classification (diagnostic triage) and the use of diagnostic and therapeutic interventions. Consistent features for acute low back pain were the early and gradual activation of patients, the discouragement of prescribed bed rest and the recognition of psychosocial factors as risk factors for chronicity. For chronic low back pain, consistent features included supervised exercises, cognitive behavioural therapy and multidisciplinary treatment. However, there are some discrepancies for recommendations regarding spinal manipulation and drug treatment for acute and chronic low back pain. The comparison of international clinical guidelines for the management of low back pain showed that diagnostic and therapeutic recommendations are generally similar. There are also some differences which may be due to a lack of strong evidence regarding these topics or due to differences in local health care systems. The implementation of these clinical guidelines remains a challenge for clinical practice and research.